Analisis Senyawa Saponin pada Ekstrak Etanol Daun Pacing Tawar (Costus speciosus) - Fitriani Fitriani; Wury Damayantie; Murtiyana Sari (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Pacing tawar is one of many plants used in alternative medicine. Pacing tawar is often used as an ingredient in herbal remedies for various ailments. Pacing leaves are effective as a remedy for itching, insect bites, and hair growth. This study aims to identify the presence and class of secondary metabolites in the ethanol extract of pacing tawar leaves to find bioactive compounds that have the potential to have pharmacological and therapeutic activities. Extraction was carried out by the maceration method using 96% ethanol solvent until a thick extract was obtained. Next, phytochemical screening was carried out to identify the content of alkaloids, flavonoids, saponins, tannins, and steroids. The test results showed that the extract of pacing tawar leaves was positive for alkaloids, saponins, tannins, and steroids, and negative for flavonoids. The alkaloid test showed a dark pink color change, the saponin test produced a 2 cm high foam for 30 seconds, the tannin test produced a dark green color, and the steroid test showed a faint red ring. Based on these results, it can be concluded that freshwater pacing leaves contain various bioactive compounds that have the potential to be developed as natural medicinal ingredients.